O estado e políticas públicas: trilhos, estradas, fios e genes da modernização do território goiano - BORGES, Júlio César Pereira (2007)
This works intends to promote a discussion about the actuation of the State, by the public politics, in the modernization of the Goiano territory, using the example of South-west micro region, by its importance in this purpose. To give a believable to this discussion, we‟ll use the researches made by contemporary scientists of Geography, that refers to this subject, as well as a study of quantitative sources, documental sources, raised of a analyze of the Goianos scientists that study this subject. We still organized interviews with some profession-als, stimulating questions by means of their publications about this theme, specially, the rea-sons that the State interfere in the modernization of the territory. This discussion has like a support, the analyzing of the State like an agent able to re-create the big homestead, able to concentrate the gain, able to disperse the cooperation systems, able to tail off the man and create a culture and a subjectivity far way the life. This fact commands thinking about the ideological and politics sense of the State and of the public politics, considering that the pub-lic politic is a ideological, financial way that put machines, lines and politics to develop an approximation between the places and the capitalist word. In this way, we tried to think about some ideas that pass up the politic and economic limits, putting a discussion about the cultural version of that process with an effective connection to the economic sense of the State and to the economic culture‟s sense, beside the politic sense of the economy. In this way, the territo-ry comes like a resume of these points: politics, economy and culture. We still considered that the social condition of the contemporary chap that lives in Goiás, in his work action, by way he insert in the urban space or rural space, by his connection with the institutions like school, public health, by his contact with the world, by phone, internet, communication, habits he has, he suffers management action done by the State. And the use of the territory is connected to the public politic and with the central matter: the State. And something more: it is occurring a lot of impacts that reconstitute the social contradictions to people that lives here. These con-tradictions go into the life, home, eating, working and, into the dreams.